Personalized medicine in a community health system: the NorthShore experience - David, Sean P.; Dunnenberger, Henry M.; Choi, Sarah; DePersia, Allison; Ilbawi, Nadim; Ward, Christopher; Wake, Dyson T.; Khandekar, Janardan D.; Shannon, Yvette; Hughes, Kristen; Miller, Nicholas; Mangold, Kathy A.; et al. (Frontiers in Genetics, 2023)
Genomic and personalized medicine implementation efforts have largely centered on specialty care in tertiary health systems. There are few examples of fully integrated care that spans the healthcare continuum. In 2014, NorthShore University HealthSystem launched the Center for Personalized Medicine to catalyze the delivery of personalized medicine. Successful implementation required development of a scalable family history collection tool, the Genetic and Wellness Assessment (GWA) and Breast Health Assessment (BHA) tools; integrated pharmacogenomics programming; educational programing; electronic medical records integrations and robust clinical decision support tools. To date, more than 225,000 patients have been screened for increased hereditary conditions such as cancer risk through these tools in primary care. Greater than 35,000 patients completed clinical genetic testing following GWA or BHA completion. An innovative program trained more than 100 primary care providers in genomic medicine, activated with clinical decision support and access to patient genetic counseling services and digital healthcare tools. The development of a novel bioinformatics platform (FLYPE) enabled incorporation of genomics data into electronic medical records. To date over 4,000 patients have been identified to have a pathogenic or likely pathogenic variant in a gene with medical management implications. Over 33,000 patients have clinical pharmacogenomics data incorporated into the EHR supported by clinical decision support (CDS) tools. This manuscript describes the evolution, strategy, and successful multi-specialty partnerships aligned with health system leadership that enabled the implementation of a comprehensive personalized medicine program with measurable patient outcomes though a genomics-enabled learning health system model that utilizes implementation science frameworks.